Insights into life after sport for Spanish Olympians: Gender and career path perspectives - Barriopedro, M.; López de Subijana, C.; Muniesa, C. (PLOS ONE, 2018)
The aims of this study were: i) to examine if Dual Career (DC) pathways are independent of gender, ii) to evaluate whether those athletes who followed a DC experienced less difficulty in their integration into the labor force than the athletes devoted entirely to sport regardless of gender, as well as iii) to analyze whether the type of career path chosen was related with the current labor status, and if differences exist between men and women athletes. A quantitative, cross-sectional, and descriptive study was used based on an ad hoc questionnaire. Two-hundred and twenty-eight retired Olympic athletes completed a questionnaire. The response rate was 28.3%. Athletes who followed a DC with studies had a higher educational level at retirement than those devoted solely to sport and those who followed a DC with work, (?2(6) = 38.76; P < .001), but no differences were found between men and women (?2(3) = 3.23; P = .358). Athletes who followed a DC path (with studies or with work) perceived the transition out of sport more positively than those who focused solely on sport (?2(2) = 7.79; P = .020). Regarding the type of job, more women attained a part-time job (20.9%) than men (3.1%; ?2(5) = 21.83; P = .001). The athletes who followed a DC with studies achieved higher monthly incomes than the other two groups (?2(2) = 9.08; P = .011). Men athletes achieved higher incomes than women (Z = 5.45; P < .001), but the gender wage gap was apparent for those Olympian athletes considered as the qualified group, probably due to a higher presence of part-time women workers. The findings of this study suggest that future professional opportunities and the transition to the labor market could be made easier by following a DC during the mastery stage. Regardless of career path, women experienced more difficulties in their integration into the job market and there is a wage penalty for highly-qualified women.